Instynkt – naśladownictwo – myślenie. Jak się uczą zwierzęta - Korpikiewicz, Honorata (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
In the article one considered bases of keeping himself animals in different living standards – during the care over young, in the play, on hunting and at dissolving more difficult problems. One underlined that the conviction about directing himself reflexes and „an instinct”, in the light of many present observations had appeared inadequate. Animals learn across the imitation and the observation of behaviour both representatives of their own sort as and other sort, eg. the man, and the trial method and errors – „the concrete thinking”. Observations show that there, where this is inadequate to dissolving of the problem, try to keep impromptu logical, similarly if this was made by the man, thinking abstractly. The statement so that with the thought and have the consciousness is not groundless anthropomorphism.